Healthy Food Literacy: How Does Kalibening Agro-edu-tourism Serve as a Sustainable Learning Resource? - Agus Sutanto; Hening Widowati; Mia Cholvistari; Beny Saputra (Institute of Information Technology and Social Science (IITSS), 2025)
This community service program aims to empower the Mitra Berkah Anjani Sejahtera Women Farmers Group (KWT) in Kalibening, East Lampung, by developing an organic melonâ€“based agroedutourism model as a learning source for healthy food literacy. The approach employed is Participatory Action Research (PAR), consisting of five stages: socialization, training and mentoring on organic cultivation and technology, product diversification, digital marketing, and evaluation. Data collection methods include observation, interviews, and preâ€“post training surveys. The results indicate an increased capacity of the KWT members in organic farming practices, the use of IoT technology (Venturi Injector), and post-harvest processing. The program successfully established the â€œAgromelkaâ€ agroedutourism model, integrating organic farming, product processing (such as ice cream, nuggets, and juice), and both online and offline marketing. This model serves as a real-life learning source for communities and students about sustainable agriculture and healthy food. Conclusion: Kalibening Agroedutourism has significant potential as a contextual learning resource for healthy food literacy. The success of this model is supported by community empowerment, technological integration, and a participatory educational approach, making it a replicable model for development in other regions.